(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The existing agricultural technology for the production of lucerne seeds in various zones of the country is analyzed. The technology of cleaning and storage of lucerne seeds from seeds of quarantine and weed plants, as well as the requirements for the quality of seed material, are given